2017
DOI: 10.1177/1076029616689300
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New ELISA-Based Vasodilator-Associated Stimulated Phosphoprotein Phosphorylation Assay to Assess Platelet Reactivity Index in a Chinese Population

Abstract: The level of platelet reactivity during P2Y12-adenosine diphosphate receptor antagonist is associated with ischemic and bleeding risks following percutaneous coronary intervention in acute coronary syndrome. Determining platelet reactivity inhibition may be valuable for confirming effective platelet inhibition for individual patients and identifying patients at risk of bleeding. The enzymelinked immunosorbent assay (ELISA)-based vasodilator-stimulated phosphoprotein (VASP) assay offers unique advantages over o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…We found their results to be strongly correlated. This conclusion is in agreement with previous studies that also found the assays to be highly concordant [10][11][12]. Indeed, Ding et al reported a correlation coefficient of 0.89 between the two VASP assays in healthy volunteers, which is very close to our coefficient (0.87).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found their results to be strongly correlated. This conclusion is in agreement with previous studies that also found the assays to be highly concordant [10][11][12]. Indeed, Ding et al reported a correlation coefficient of 0.89 between the two VASP assays in healthy volunteers, which is very close to our coefficient (0.87).…”
Section: Discussionsupporting
confidence: 94%
“…The 2010 Working Group on High On-Treatment Platelet Reactivity, the 2015 Working Group on Thrombosis of the European Society of Cardiology, and the 2019 Expert Consensus on Platelet Function and Genetic Testing for Guiding P2Y 12 Receptor Inhibitor Treatment each published position papers on platelet function testing in patients on P2Y 12 inhibitors. These papers suggested that platelet function could be tailored within a therapeutic window to balance ischemic versus bleeding complications [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Further differences between these tests should be based on their sensitivity and specificity in predicting atherothrombotic events after percutaneous coronary intervention (PCI), as well as their cost and labor intensity. 3,15,16 The VASP assay is the only specific test for P2Y12 inhibition and is not affected by the effect of ADP on the P2Y1 receptor. It is measured with the platelet reactivity index (PRI).…”
Section: Platelet Function Testmentioning
confidence: 99%
“…This assay has been standardized, but the disadvantage is that this method needs a few steps for the testing, which is timeconsuming and costly. 16 Several studies have predicted thrombotic events by investigating the cut-off PRI value. Bonello et al were the first to use the VASP assay to determine the correlation of HRPR with clopidogrel and clinical incidence.…”
Section: Platelet Function Testmentioning
confidence: 99%
See 1 more Smart Citation